Disclosure, trust and persuasion in insurance markets - David de Meza; Bernd Irlenbusch; Diane Reyniers (Institute for the Study of Labor (IZA), 2010)
This high-stakes experiment investigates the effect on buyers of mandatory disclosures concerning an insurance policy's value for money (the claims ratio) and the seller's commission. These information disclosures have virtually no effect despite most buyers claiming to value such information. Instead, our data reveal that whether the subject is generally trusting plays an important role. Trust is clearly associated with greater willingness to pay for insurance. Unlike in previous work, trust in our setting is not about obligations being fulfilled. The contract is complete, simple and the possibility of breach is negligible. However, as for much B2C insurance marketing, face-to-face selling plays a crucial role in our experimental design. Trusting buyers are more suggestible, so take advice more readily and buy more insurance, although they are no more risk averse than the uninsured. Moreover, trusting buyers feel less pressured by sellers, and are more confident in their decisions which suggests that they are easier to persuade. Therefore, in markets where persuasion is important, public policy designed to increase consumer information is likely to be ineffective.
Keywords: C91; G22; M30; 330; insurance selling; trust; persuasion; Versicherung; Konsumentenverhalten; Versicherungsvermittlung; Vertrauen; Informationsverhalten; Publizitätspflicht; Versicherungsrecht; Theorie